RELATIONSHIP COMMITMENT DAN CUSTOMER ENGAGEMENT: STIMULUS SERTA KONSEKWENSI PADAKONSUMEN PENGGUNA TRANSPORTASI DARAT - Sri Vandayuli Riorini; Christina Catur Widayati (MIX: JURNAL ILMIAH MANAJEMEN, 2015)
Abstract.The purpose of carrying out this research is to analyze the stimulus andconsequence of Relationship commitment and Customer engagement. Moreover, integratedlybe able to analyze the effect of Trust, Relationship commitment, Customer engagementtowards Repurchase intention on 200 respondents of AKAP Bus user who uses the interprovincebus services minimum 2 in the past 6 months using Purposive Sampling technique,and analyzing method using Structural Equation Model technique. The result of the researchfinds:(1) Positive effect of Cognitive trust, Affective trust towards Relationship commitment,Customer engagement, Repurchase intention; (2) Positive effect of Relationshipcommitment, Customer engagement towards Repurchase intention; (3) Relationshipcommitment, Customer engagement is seen as the mediator in relationship among Cognitivetrust, Affective trust and Repurchase intention; (4) Affective trust is the biggest stimuluseffecting Relationship commitment, Customer engagement; and(5) Repurchase intention isthe consequence of Relationship commitment and Customer engagement, however, Customerengagement has bigger effect on Repurchase intention. On future research, it is advisable toadd Service quality and Customer satisfaction variables as stimulus of Relationshipcommitment and Customer engagement.Keywords: Cognitive trust, Affective trust, Relationship commitment, Customer engagement,Repurchase intention